Making Micronesia A Political Biography of Tosiwo Nakayama - Hanlon, David L. (University of Hawaii Press, 2014)
The study of his life also invites a reconsideration of migration, transnational crossings, and the actual size of island worlds. Making Micronesia follows Nakayama’s life through time, focusing on the expansiveness of his vision. In many ways, "Macronesia," not "Micronesia," seems a more appropriate term for the world he inhabited and tried to make accessible to others
Description based on online resource; title from PDF title page (publisher's Web site, viewed 21. Nov 2017)
Keywords: Nakayama, Tosiwo -- 1931-2007; Presidents -- Micronesia (Federated States) -- Biography; Biografie